Febrile Status Epilepticus - Molinero, Isaac; Shinnar, Shlomo (Journal of Pediatric Epilepsy, 2019)
Febrile status epilepticus (FSE) is defined as a febrile seizure lasting 30 minutes or more and is considered the extreme end of the complex febrile seizure spectrum. It remains unclear why some children are predisposed to the development of FSE compared with others. FSE is considered as medical emergency and as such, early treatment is crucial. The consequences of FSE have been a topic of interest for many years, specially its association with temporal lobe epilepsy and hippocampal sclerosis. In this article, we review the epidemiology, risk factors, pathophysiology, treatment, and prognosis including findings from the “Consequences of Prolonged Febrile Seizures in Childhood” (FEBSTAT) study.
Keywords: seizures; epilepsy; febrile seizures; febrile status epilepticus